JQuery for designers : beginner's guide - MacLees, Natalie (Community experience distilled., 2012)
In Detail jQuery is awesome for designers - it builds easily on the CSS and HTML you already know and allows you to create impressive effects with just a few lines of code. However, without a background in programming, JavaScript - on which jQuery is built - can feel intimidating and impossible to grasp. This book will show you how simple it can be to learn the basics and then extend your capabilities by taking advantage of jQuery plugins. jQuery for Designers offers approachable lessons for designers with little or no background in JavaScript. The book begins by introducing the jQuery library and a small and simple introduction to JavaScript. Then you'll step through a few simple tasks to get your feet wet before diving into using plugins to quickly and simply add complex effects with just a few lines of code. You'll be surprised at how far you can get with JavaScript when you start with the power of the jQuery library and this book will show you how. We'll cover common interface widgets and effects such as tabbed interfaces, custom tooltips, and custom scrollbars. You'll learn how to create an animated navigation menu and how to add simple AJAX effects to enhance your site visitors' experience. Then we'll wrap up with interactive data grids which make sorting and searching data easy. Approach Part of Packt's Beginner's Guide series, each chapter focuses on a specific part of your website and how to improve its design with the use of jQuery. There are plenty of screenshots and practical step-by-step instructions making it easy to apply jQuery to your site. Who this book is for This book is for designers who have the basics of HTML and CSS, but want to extend their knowledge by learning to use JavaScript and jQuery.